Programa de monitoramento auditivo de crianças com indicadores de risco para a deficiência auditiva - Araújo, Mara Rosana (2009)
Introduction Audiologic monitoring of infants with risk indicators for hearing loss has been recommended and discussed in several studies, however there is not a strict protocol. Objective To analyze the results of an audiologic follow-up program for children at risk for hearing loss. Method We studied 127 children with risk indicators for hearing loss who had a normal newborn hearing screening. It was chosen the visual reinforcement audiometry technique to evaluate hearing for children from six to 24 months. The children who could not perform the visual reinforcement audiometry were submitted to the behavioral observation audiometry technique. Children older than 24 months were evaluated with conditioned play audiometry. And, the OAE was performed in children who did not accept the insert earphones. Children with suspected hearing loss had appointments for new evaluation, and those with abnormal results were submitted to an ABR. Results The most frequently observed risk indicators were NICU for more than 5 days (75%) and the use of ototoxic drugs (63%). Ninety two (72.4%) of the 127 children analyzed attended at least one session of audiologic monitoring. The mean age in the first, second and third sessions were 13.2, 20.6 and 32.6 months, respectively. Regarding the behavioral assessment techniques, most of the children (95.6%) were able to perform VRA. Among them, 71.6% accepted the insert earphones. Only 28.4% did not accept the earphones, being tested through VRA in free field. In the three steps of this audiologic monitoring 14 children (15.2%) had suspected hearing loss, three of which have been identified with conductive hearing loss. Conclusion In the first session, 72.4% of children who scheduled appointments were present. Almost 71.7% of children missed the second appointment and the 80.7% the third session. The VRA was a viable technique for monitoring hearing, performed in 95.6% of the children. We found three cases (3.2%) of conductive hearing loss, ranging from mild to moderate